Tips for Overcoming Legal Problems for Small and Micro Enterprises in the Karangrejo Market Trader Community - Waskito, Sarwo; Purborini, Vivi Sylvia (Civiliza Publishing, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in strengthening the people's economy nationally, so the government must pay attention to strategies and policies for empowering MSMEs. This article discusses the problems of developing MSMEs in order to improve people's welfare, forms of exploitation of MSMEs and forms of legal protection for MSMEs. Socialization was carried out at the Karangrejo market offline. The results of the socialization showed that the problems of developing MSMEs covered several things such as marketing difficulties, financial limitations, human resource limitations, raw material problems, and technological limitations. Meanwhile, the pattern of exploitation of MSMEs covered capital accumulation, the creation of economic and social dependency, and a monopolistic market structure. Until now, the form of legal protection for MSMEs provided by the government is through simplifying the requirements and procedures for applying for business permits, development procedures, partnership patterns, organizing coordination and control of MSME empowerment, and procedures for imposing administrative sanctions. From the conclusion, the government is recommended to make further arrangements, related to legal protection for MSMEs, supervise parties who cheat, and provide better legal protection for MSMEs. In addition, the state should carry out reforms, one of which is by providing free legal assistance for MSMEs and tax deductions.